Clinical Comparison between Native Vertebral Osteomyelitis with Abscess vs Without Abscess in Clinical Features and Outcomes. (4th October 2017) - Matsuo, Takahiro; Mori, Nobuyoshi; Hoshino, Eri; Sakurai, Aki; Furukawa, Keiichi
Abstract: Background: It is well documented that native vertebral osteomyelitis (NVO) is accompanied by abscess formation (epidural, paravertebral, and psoas muscle) that is complicated by neurological deficit. There are few studies comparing between NVO with abscess and NVO without abscess in clinical features and outcomes. Methods: We conducted a retrospective cohort study at St. Luke's Intl. Hosp. in Tokyo, Japan (acute care hospital, 520 beds) from 2004 to 2015. Diagnosis of acute NVO was made by clinical signs and symptoms, and MRI. Clinical features and outcomes of NVO patients with abscess were compared with ones without abscess. Fisher's exact test, Mann–Whitney U -test, and Kaplan–Meier curve with log-rank test were used in univariate analysis and the association to length of stay was analyzed by Cox-regression model controlling confounding. Results: Among 122 patients with NVO, 83 patients (68%) had abscess (group A) and 39 patients (32%) had no abscess (group B). Median age: (group A: 69 vs. group B: 66, P = 0.641). Median length of stay (LOS) in hosp: (A: 48 vs. B: 43 days, P = 0.007) (Table 1). Group A had higher rate of neurological symptoms (16.9 vs. 2.6%, P = 0.035), blood cultures positivity (62.7 vs. 35.9%, P = 0.007), infective endocarditis (IE) (15.7 vs. 2.6%, P = 0.036), and longer duration of therapy (75 vs. 56 days, P = 0.025) than group B in univariate analysis. Also, group A had trend toward higher rate of methicillin-susceptible S. aureus (28.9 vs. 5.1%, P = 0.056). Kaplan–Meier analysis revealed LOS was significantly longer in group A ( P = 0.013) (Figure 1). The result of Cox's proportional hazards model suggested abscess was associated with longer LOS (Table 2). Blood culture positivity was independently associated with longer LOS. No statistically significant associations were observed between abscess and 90-day mortality (5.1 vs. 3.6%, P = 0.654), or neurological sequelae (6 vs. 0%, P = 0.227). Conclusion: LOS of NVO patients with abscess was longer than those without abscess. In particular, LOS was significantly longer in patients with positive blood culture than those with negative results. Disclosures: All authors: No reported disclosures.